Stress of Nurses during the COVID-19 Pandemic: A Literature Review - Gunawan; Yuly Peristiowati; Agusta Dian Ellina (GoAcademica Research & Publishing, 2021)
The COVID-19 pandemic is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2), has caused a total of 1,531,005 people in Indonesia confirmed positive for COVID-19 and 42,000 people died. The increasing number of COVID-19 cases in Indonesia has made nurses stress as front-liner. This study aims to identify the description of stress in nurses. This study is a systematic literature review by identifying cross-sectional study, published in 2019-2021, in English and Indonesian, and full-text. The electronic database that used was Google Scholar with the keywords “Nurses” AND “Stress” AND “COVID-19”. The results obtained 10 articles that related to stress in nurses and factors that caused it. All of studies stated that nurses were stress from mild to severe. Demographic factors that caused stress include age, gender, education level, having children, working status, and years of services. Meanwhile, situational factors were the inconvenience of continuous and strict use a personal protective equipment, being in isolation room, lack of understanding in treating COVID-19 patients, fear of being infected and transmitting the virus to family, and homesickness. An adaptive coping mechanism is needed to reduce stress levels for nurses as the front line in the COVID-19 pandemic.